2014
DOI: 10.2478/jlecol-2014-0010
|View full text |Cite
|
Sign up to set email alerts
|

Roads and Roadless Areas in Cyprus: Implications For The Natura 2000 Network

Abstract: The road network in Cyprus has seen an 88% increase in the last 20 years. This expansion has not been followed by any kind of assessment on the effects of the network on nature conservation. This is the first island-wide quantitative assessment of the size, character (surface types), pervasiveness and distribution of the road system with particular reference to Natura 2000 network on the island. We mapped roadless areas (i.e. areas at least one km away from nearest road) for the whole island and examined the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…The combination of noise with fragmentation maps identified many areas with high and very high impact (hotspots), containing 11 SPAs under the Natura 2000 network of protected areas which present significant risk for Cyprus's avifauna, where mitigation actions should be taken. This corroborates with the results from other studies on the island on the pervasiveness of the road network on protected areas (Zomeni and Vogiatzakis 2014;Mammides et al 2015).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The combination of noise with fragmentation maps identified many areas with high and very high impact (hotspots), containing 11 SPAs under the Natura 2000 network of protected areas which present significant risk for Cyprus's avifauna, where mitigation actions should be taken. This corroborates with the results from other studies on the island on the pervasiveness of the road network on protected areas (Zomeni and Vogiatzakis 2014;Mammides et al 2015).…”
Section: Discussionsupporting
confidence: 92%
“…Cyprus is an island with special importance for ornithology because it is situated along one of the main migratory routes for birds, which has resulted in a rich and diverse avifauna. At the same time, it is among the countries in Europe with the highest road densities (Zomeni and Vogiatzakis 2014) and where the road network is expanding (Statistical Service of Cyprus data). This is the first large scale/island-wide study looking at the combined effects of traffic noise and road induced fragmentation on bird richness.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Mehdipour et al (2019) found that the construction of roads has led to subdivision in the Ghamishloo National Park and Wildlife Refuge, as indicated by an increase in SPLIT and DIVISION and a decrease in MESH and LPI. Research on the effects of roads on landscape characteristics (Jaeger et al, 2008;Zebardast et al, 2011;Zomeni and Vogiatzakis, 2014) similarly found that roadinduced decrease in MESH and increase in SPLIT and DIVISION are indicative of increased fragmentation and pose a threat to species which require large areas to survive as smaller patches jeopardize their survival.…”
Section: Discussionmentioning
confidence: 99%
“…Uniform plots of each habitat type were identified in the field and delineated using a handheld GPS device. Because of the high habitat fragmentation along the target regions (Zomeni and Vogiatzakis 2014;P. Panayides 2006, unpublished manuscript), random selection of plots would have resulted in mixtures of habitats, thus we opted for study area selection through work in the field to ensure uniform plots were targeted.…”
Section: Population Surveysmentioning
confidence: 99%